Novel copper complexes with glyoximes, amines, schiff bases, semi-and thiosemicarbazones ; synthesis and physico-chemical analysis - Várhelyi Csaba; Szalay Roland; Pokol György; Madarász János; Szilágyi Imre Miklós; Huszthy Péter; Simon-Várhelyi Melinda; Tötös Róbert; Mereu Raluca-Anca; Avram Alexandra; Korecz László; May Nóra V.; et al. (2022)
In our research project new copper(II) complexes were synthesized with -dioximes, amines, Schiff bases, semi- and thiosemicarbazones such as [Cu(DioxH)2L2], (DioxH2: methyl-butylglyoxime, ethyl-butyl-glyoxime, methyl-phenyl-glyoxime; L: diphenyl-amine, 2-methylimidazole, dibutyl-amine, 2-amino-4-methylpyridine, imidazole, 1-aminonaphthaline), [Cu(octan-2-one)2AL2], (A: hydrazine, phenylhydrazine, o-phenylene-diamine; L: 3-amino1H-1,2,4-triazole, 2-aminopyrimidine, 2-methylimidazole), [Cu(ketone-SC)2], [Cu(ketoneTSC)2], (ketone: propiophenone, butyrophenone; SC: semicarbazone; TSC: thiosemicarbazone), by the reaction of copper(II)-acetate in suitable solvent. After a short bibliographical survey, involving the classification and evolution of copper complexes with possible applications, we analyzed their physicochemical properties using FTIR, Raman, ESR, UV-VIS, powder X-ray diffraction (XRD), mass spectrometry, thermal analysis (TG, DTG, DTA) and SEM. The importance of this class of compounds lies in biochemistry as some of them are antibacterial agents and potential anti-tumour drugs.
Keywords: Természettudományok; Kémiai tudományok